Качество банковских кредитов и его взаимосвязь с качеством банковских кредитных услуг - Плотникова, М.В. (Культура народов Причерноморья, 2013)
Статья посвящена изучению качества банковских кредитов как особого объекта банковского управления, что является особенно актуальным в связи с последствиями кризисных явлений в банковском секторе. На основе анализа различных точек зрения на понятие «качество кредитов» сделана попытка рассмотреть категорию «качество банковских кредитов», учитывая экономическую природу банковского кредита и его сущностные свойства как стоимостной категории. Показана взаимосвязь качества банковских кредитов с качеством банковских кредитных услуг на основе особых сущностных характеристик кредита. Стаття присвячена вивченню якості банківських кредитів як особливого об'єкта банківського управління, що є особливо актуальним у зв'язку з наслідками кризових явищ у банківському секторі. На основі аналізу різних точок зору на поняття «якість кредитів» зроблена спроба розглянути категорію «якість банківських кредитів», враховуючи економічну природу банківського кредиту та його сутнісні властивості як вартісної категорії. Показано взаємозв'язок якості банківських кредитів з якістю банківських кредитних послуг на основі особливих сутнісних характеристик кредиту The article is devoted to studying the quality of the bank credits as a special object of bank management that is especially topical in connection with consequences of the crisis in the banking sector. The analysis of the various points of view about the concept “credit quality” is carried out. It is found out that some authors identify the concepts “credit quality” and “quality of credit portfolio”; others define quality of the credits as an estimated indicator or the set of indicators. The author made an attempt to consider the category “bank credit quality” considering the economic nature of the bank credit and its intrinsic properties as a value category. It is found out that repayment is a fundamental criterion of quality of all credits. It is revealed that preservation of the lent value is a special property of the bank credit and also it characterizes the quality of the bank credits. The analysis of the principles of bank crediting and their correlation with quality of the bank credits is carried out. It is shown that the principles of maturity and interest payment have a special impact on quality of the bank credits, and the principles of goal orientation, security, and personal approach are not so significant. It is found out that the credit allows accelerating repayment process and creating an additional surplus value both for the creditor and the borrower. On this basis the interrelation of quality of the bank credits with quality of banking credit services with special intrinsic characteristics of the credit is shown.